Investigating the Impact of Monetary Policy using the Vector Autoregression Method - Salmanov, Oleg Nikolayevich; Zaernjuk, Victor Makarovich; Lopatina, Olga Alekseevna; Drachena, Irina Petrovna; Vikulina, Evgeniya Viktorovna (International Journal of Economics and Financial Issues, 2016)
Careful identification of the transmission channels of monetary policy is an important step in the global assessment of the major institutional changes. Research in this area should be constantly updated because of the strong structural dynamics. The goal of this paper is to study the monetary transmission in the Russian economy. The study was carried out using the vector autoregression method (VAR). The analysis of impulse functions of interest rate shocks, corporate lending, volume of money supply, growth of prices and the exchange rate was carried out. An interpretation of the transmission channels of the Russian economy was given. The following channels were considered: interest rate, bank lending, cash flows, unforeseen prices and the exchange rate channel. All channels under consideration are statistically confirmed, but they exist with varying degrees of effectiveness. The existence of weak channels of monetary transmission is associated with the depressive state of the economy, lack of its growth in recent years, and high inflation, as well as with the policy of shift from the ruble rate targeting to the inflation targeting policy. The outcomes of use of the standard VAR methods for the developing Russian economy can be used as a guideline for further theoretical and empirical analysis of the transmission mechanism Keywords: monetary policy, vector autoregression, impulse functions. JEL Classifications: E52, E58